Magnetic Properties of Australasian Tektites From South China. Issue 3 (20th March 2023) - Pan, Qing; Xiao, Zhiyong; Wu, Yunhua; Shi, Taiheng; Yin, Zongjun; Yan, Pan; Li, Ye
Abstract: South China, the northern part of the Australasian strewn field (AASF) of tektites and microtektites is located at the uprange of the hypothesized source crater that is still unconfirmed. Magnetic properties of impact glasses are an important indicator of their source materials and thermal history. Extensive magnetic investigations have been performed on various AASF tektites sampled from both the Indochina Peninsula and further south, but such information remains sparse for those sampled from South China. Here, we present a detailed rock magnetism study for both Muong Nong‐type and splash‐form AASF tektites from South China, showing that all the tektites have rather weak remanent magnetization, but ferromagnetic information can be extracted from their dominating paramagnetic signal. Signals caused by superparamagnetic particles are elusive, but those of single domain magnetite are detected in the splash‐form tektites, and signals of pseudo‐single domain magnetite are discovered in the Muong Nong‐type tektites. Each morphological type of tektites from a same geographic area exhibits large dispersions in their magnetic properties. Across the entire AASF, the Muong Nong‐type tektites from South China exhibit the lowest average magnetic susceptibility, and the splash‐form tektites exhibit the smallest average natural remanent magnetization and ratio of equivalent magnetization. The observed heterogeneous magnetic properties are mainly caused by the different contents and sizes of magnetic particles, which can be explained by the different shock level and/or cooling history of the tektite melts. Micro‐sized immiscible Fe‐S spherules in the Muong Nong‐type tektites from South China were likely originated from the pre‐impact target. Plain Language Summary: About 0.78 million years ago, an about 1 km diameter asteroid or comet ended its trajectory on Earth. Instantaneously, massive continental sediments were molten and ejected, and natural glasses (tektites) were quenched and deposited across vast areas over 1 × 10 8  km 2, forming the largest known Cenozoic strewn field of tektites and microtektites, the Australasian strewn field (AASF). The impact site is still unconfirmed. Magnetic properties of impact glasses are indicative to their source materials and thermal history. This study presents the first rock magnetic measurements for AASF tektites from South China. We find that while the samples are dominated by paramagnetic signals, signals caused by single domain magnetite are detected, and the Muong Nong‐type tektites contain pseudo‐single domain magnetite. Signals of superparamagnetic grains are elusive. With heterogeneous magnetic properties, tektites from South China generally exhibit lower magnetic susceptibility, natural remanent magnetization, and ratios of equivalent magnetization than the rest of AASF. The observed magnetic properties can be explained by different shock levels and cooling histories of the tektite melts, but strong magnetic field(s) recorded by some Muong Nong‐type tektites have an unknown origin. The first occurrence of Fe‐S spherules in tektites from South China might originate from target materials. Key Points: The first comprehensive rock magnetism study is performed for both splash‐form and Muong Nong‐type tektites from South China Samples from China generally exhibit lower magnetic susceptibility, natural remanent magnetization, and ratio of equivalent magnetization Different shock levels and cooling histories of tektite melt can explain the observed magnetic properties, and Fe‐S spherules are found